2016
DOI: 10.1093/eurheartj/ehw506
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of left ventricular global longitudinal strain in heart failure patients with narrow QRS complex treated with cardiac resynchronization therapy: a subanalysis of the randomized EchoCRT trial

Abstract: Bax, J. J. et al. (2017) Prognostic implications of left ventricular global longitudinal strain in heart failure patients with narrow QRS complex treated with cardiac resynchronization therapy: a subanalysis of the randomized EchoCRT trial. European Heart Journal, 38(10), pp. 720-726.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/139629/ patients in the CRT-OFF group and 111 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…When possible, 3D echocardiograms were obtained, but these were not clinically feasible in a significant number of patients and were not used for clinical decision making. Myocardial strain imaging was obtained from the apical 4-chamber, 2-chamber, and long-axis views to determine global longitudinal strain (GLS), as described previously in detail (GE EchoPac v200, Horton, Norway) (17).…”
Section: Louis Frommentioning
confidence: 99%
“…When possible, 3D echocardiograms were obtained, but these were not clinically feasible in a significant number of patients and were not used for clinical decision making. Myocardial strain imaging was obtained from the apical 4-chamber, 2-chamber, and long-axis views to determine global longitudinal strain (GLS), as described previously in detail (GE EchoPac v200, Horton, Norway) (17).…”
Section: Louis Frommentioning
confidence: 99%
“…47 A recent study suggested that 17-34% of patients with HFrEF or HFmrEF improve to a higher category, and that this, as expected, was more common in the absence of ischaemic heart disease. 48 Other modalities may refine characterization of HF, such as global longitudinal strain, 49,50 but their impact in clinical routine remains to be seen. Given the heterogeneity of HF and difficulty characterizing HF, in particular with preserved EF, multimarker personalized approaches to HF, as occurs in oncology, may improve characterization and classification in HF.…”
Section: -38mentioning
confidence: 99%
“…Echocardiographic strain by speckle-tracking precisely characterizes left ventricle performance [7], scar burden [8], and dyssynchrony [9]. Left ventricle global longitudinal strain (LVGLS) is associated with the outcome in general population [10] as well as in heart failure patients [11]. Previous studies have demonstrated that baseline left ventricle function stays in relation Michal Orszulak and Artur Filipecki contributed equally to this manuscript.…”
Section: Introductionmentioning
confidence: 99%